The role of evidence, standards and education in rock fishing safety in New South Wales, Australia. (28th August 2014) - Mitchell, Rebecca J.; Ware, Lauren; Bambach, Mike R.
Abstract Objective: To examine rock fishing‐related fatalities and hospitalisations, identify initiatives aimed at improving safety and survey key rock fishing stakeholders about the strengths and limitations of each initiative. Method: This research obtained information from mortality and hospitalisation statistics, the published literature and key stakeholders for opinions on the strengths, limitations and improvements for rock fishing safety initiatives. Results: Injury patterns involving rock fishers have largely remained unchanged over time. The literature revealed that many rock fishing safety initiatives focused on awareness raising and engineering initiatives, but ignored the development of guidelines and the use of enforcement strategies. There had been limited evaluations conducted of any of the initiatives reviewed. Conclusions: It is likely that a combination of evidence‐based, standard‐focused and education initiatives would be useful in improving rock fishing safety in NSW, provided that the impact of these initiatives were routinely evaluated. Implications: Information from this research will be used to inform preventive strategies aimed at improving rock fishing safety through better coordination of the role of evidence in informing standards and practices and the continued evaluation of these initiatives.